Do our doctors and nurses cope well with their stress? - Mohamed, Mahmood Nazar; Marican, Sabitha (Universiti Utara Malaysia, 1999)
Stress exists in all spheres of life. One which is most researched is stress related to work. This study investigates the experience of stress among the health profession in the state of Kedah and how they cope with the stress. Data was collected from a total of 346 doctors, nurses and administrators by using Demographic Profile Questionnaire, Stress Inventory (Gmelch, 1982) and the COPE Scale (Carver, Scheier & Weintraub, 1989). The most common stressors are of organizational type, that is, the health professionals feel stressed by their role conflict, by limitations in the organizational structure and by the amount of workload. Overall, stress that originates from family and their own personal life ranked fourth. As for coping strategies, most of the health professionals turn to religion (such as praying and meditating) when they feel stressed followed by some cognitive-behavioral approach such as planning, strategizing and directly handling the problem at hand. Poor coping strategies such as the use of denial (defense mechanism) and drugs were not preferred and were least used as a form of coping strategy. This study concluded that health professionals in the state of Kedah faced some organizational—type stress and used health coping mechanism to overcome their stress.